2023
DOI: 10.31223/x5s05f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust Probabilities of Detection and Quantification Uncertainty for Aerial Methane Detection: Examples for Three Airborne Technologies

Abstract: Thorough understanding of probabilities of detection (POD) and quantification uncertainties is fundamentally important when applying aerial measurement technologies as part of alternative means of emission limitation (AMEL) or alternate fugitive emissions management programs (Alt-FEMP), as part of monitoring, reporting, and verification (MRV) efforts, and in surveys designed to support measurement-based emissions inventories and mitigation tracking. This paper presents a robust framework for deriving continuo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Finally, this approach provides the relative contribution of each stratum to the whole, which is important data for regulation and mitigation. While the present demonstration of this approach uses aerial measurement data collected using Bridger Photonics Gas Mapping LiDAR (GML), the protocol is generally applicable to any technology with well-characterized probabilities of detection (POD) and quanti cation uncertainties 25 and su cient spatial resolution to resolve individual facilities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, this approach provides the relative contribution of each stratum to the whole, which is important data for regulation and mitigation. While the present demonstration of this approach uses aerial measurement data collected using Bridger Photonics Gas Mapping LiDAR (GML), the protocol is generally applicable to any technology with well-characterized probabilities of detection (POD) and quanti cation uncertainties 25 and su cient spatial resolution to resolve individual facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Referring to Fig. 1b, this is possible via a parallel Monte Carlo simulation considering site/condition-speci c POD 25 using "bottom-up" equipment count and measurement data from prior studies (e.g., refs [29][30][31][32][33] as inputs. This new "unmeasured source" protocol allows robust derivation of stratum-dependent, average, emission factors for unmeasured sources on a per-site basis.…”
Section: Protocol For Estimating Unmeasured Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…This dataset includes measurements that are higher than 26 kg/hr, which is a threshold typically used to refer to high-emitters (also referred to as super-emitters). 14 Bridger Photonics uses a continuous wave LiDAR measurements and has been described and evaluated by Johnson et al 24 and Conrad et al 25 From this dataset, only the emissions where operators confirmed that the source was non-routine, after following-up, were included in the distribution. Sensitivity analysis S0 was performed by adding to the distribution of close range inspections data from ERG 26 and Ravikumar et al, 27 as described by Kemp et al, 13 and assigning emissions randomly from a combined distribution, independently of which equipment the data came from, except for tanks and flares where the data comes from the flyover distribution.…”
Section: Emission Measurementsmentioning
confidence: 99%